MANAJEMEN KOMUNIKASI ANTARPRIBADI DALAM PENGEMBANGAN KARAKTER SANTRI DI PESANTREN - Edi Putra Jaya; Hairul Fauzi; Suhadi Suhadi; Maryam Maryam (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the management of interpersonal communication between kiai and students in developing students’ character in Islamic boarding schools, as well as to examine the process of internalizing Islamic religious education values through such communication within the context of contemporary Islamic education. Method: This study employed a qualitative approach with a field research design. Data were collected through in-depth interviews, observations, and documentation involving kiai, boarding school administrators, and students as research participants. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing in a systematic and continuous manner. Results: The findings indicate that interpersonal communication between kiai and students occurs through both formal and informal patterns that are not yet systematically structured, yet significantly contribute to the development of students’ religious character, discipline, responsibility, and moral values. Novelty: The novelty of this study lies in positioning interpersonal communication as a managerial instrument within Islamic boarding schools that functions as an integrative bridge between educational management and Islamic religious education in fostering holistic and sustainable character development among students.